Pregnant women's responses to a tailored smoking cessation intervention: turning hopelessness into competence - Zaino Petersen; Krisela Steyn; Katherine Everett-Murphy; Maria Emmelin (Taylor & Francis Group, 2010)
Background: Cognitive behavioral interventions consisting of brief counseling and the provision of self-help material designed for pregnancy have been documented as effective smoking cessation interventions for pregnant women. However, there is a need to understand how such interventions are perceived by the targeted group. Aim: To understand the cognitive, emotional, and behavioral responses of pregnant women to a clinic-based smoking cessation intervention. Methods: In-depth interviews with women attending four antenatal clinics in Cape Town, South Africa, who were exposed to a smoking intervention delivered by midwives and peer counselors. Women were purposively selected to represent a variation in smoking behavior. Thirteen women were interviewed at their first antenatal visit and 10 were followed up and reinterviewed later in their pregnancies. A content analysis approach was used, which resulted in categories and themes describing women's experiences, thoughts, and feelings about the intervention. Results: Five women quit, five had cut down, and three could not be traced for follow-up. All informants perceived the intervention positively. Four main themes captured the intervention's role in influencing women's smoking behavior. The process started with ‘understanding their reality,’ which led to ‘embracing change’ and ‘deciding to hold nothing back,’ which created a basis for ‘turning hopelessness into a feeling of competence.’Conclusion: The intervention succeeded in shifting women from feeling pessimistic about ever quitting to feeling encouraged to try and quit. Informants rated the social support they received very highly and expressed the need for the intervention to become a routine component of clinic services.